The Effect of Transformational Leadership and Organizational Culture on The Quality of Education Services - Furtasan Ali Yusuf; Anis Fauzi; Anwar Malik (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
The main problems in this study are: (1) Is there a significant effect of transformational leadership on the quality of education services ?; (2) Is there a significant influence of organizational culture on the quality of education services? (3) Is there a significant influence of transformational leadership and organizational culture together on the quality of education services in Islamic Elementary School in Serang City? The method used in this research is a correlational quantitative method with a questionnaire research instrument. This research was conducted at Islamic Elementary School in Serang City, with a population of 207 and 82 respondents as the sample in the study. The results of this study indicate that: (1) transformational leadership can influence the formation of the quality of education services, with a correlation coefficient of "rx1y" of 0.51; (2) Meanwhile, the influence of organizational culture on the quality of education services has a correlation value of "rx2y" of 0.48; (3) The result of multiple correlation test shows the number Rx1x2y of 0.78, so the results of this study indicate acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0).